Precision Medicine for Intracranial Atherosclerotic Disease - Liebeskind, David S. (Frontiers in Neurology, 2021)
Diagnostic and therapeutic strategies for intracranial atherosclerotic disease (ICAD) have vastly expanded within the last several years. Challenges and concrete initiatives have emerged in the implementation of precision medicine for ICAD, focusing personalized treatment for the prevention of stroke and cognitive impairment around pathophysiology. Theranostics for ICAD incorporates an integrated diagnostic and therapeutic approach tailored to a specific individual. The ICAS 2019 meeting provided a roadmap for accelerating global innovation, underscoring the epidemiology, prior scientific evidence from trials, diagnostic tools or imaging, novel biomarkers, management approaches, and a broad range of treatments including many new medications, endovascular, and surgical strategies. This thematic overview provides perspective on current definitions for arterial stenosis, symptomatic lesions and outcomes or endpoints in clinical trials. Imaging correlates are reviewed, from routine multimodal CT or MRI to advanced angiographic techniques. The temporal features of ICAD and longitudinal observation are considered with respect to management and risk factor modification. The evolving science of multivariable interactions in ICAD and use of big data are explored, followed by an overview of recently launched clinical trials.